Terminal Ileal Endoscopic Findings in Chronic Diarrhoea: Experience of A Tertiary Teaching Hospital in Bangladesh (Mugda Medical College Journal, 2026)
Terminal ileal intubation is an integral part of colonoscopy in patients with chronic diarrhoea. Besides colonic diseases, terminal ileum can be involved in chronic diarrhea pathogenesis. The aim of this study was to assess the additional diagnostic yield of ileal intubation in chronic diarrhea. This cross-sectional study was conducted in the Department of Gastroenterology of National Gastroliver Institute and Hospital, Dhaka, Bangladesh, between July and December of 2021. One hundred and sixteen consecutive patients with chronic diarrhoea were enrolled. Thirteen patients were not fulfilling the inclusion criteria were excluded. In all patients, routine terminal ileal intubation was done as a part of routine colonoscopy and biopsies were taken from any visible lesion. Histopathology and GeneX-pert for detection of MTB were done from biopsy specimen. One-third (35.9%) of patients belonged to the 26-40 years age group. The mean age was 35.63±15.21 years (ranging between 18 and 74 years). Almost two-thirds (63.1%) of patients were male. More than three fourth (77.9%) of the patients were nonsmoker. In this study, isolated macroscopic abnormal ileum was found in 12(11.65%) patients and 13(12.62%) patients had macroscopic abnormality in both ileum and colon, which gave a diagnostic yield of 24.27% of all ileal intubation. No association was observed between macroscopic features and age or gender of the patients (p>0.05); however, significant association was found between macroscopic features and alarming features of the patients (p=0.001).Mugda Med Coll J. 2026; 9(1): 3-8